Effect of ADAMTS‐13 on cerebrovascular microthrombosis and neuronal injury after experimental subarachnoid hemorrhage. (April 2014) - Muroi, C.; Fujioka, M.; Mishima, K.; Irie, K.; Fujimura, Y.; Nakano, T.; Fandino, J.; Keller, E.; Iwasaki, K.; Fujiwara, M.
Summary Background Microthrombosis and reactive inflammation contribute to neuronal injury after subarachnoid hemorrhage (SAH). ADAMTS‐13 cleaves von Willebrand factor multimers, and inhibits thrombus formation and, seemingly, inflammatory reactions. Objective To investigate the effect of ADAMTS‐13 in experimental SAH. Methods A total of 100 male C57/BL6 mice were randomly assigned to four groups: sham (n = 15), SAH (n = 27), vehicle (n = 25), and ADAMTS‐13 (n = 23; 100 μL per 10 g of body weight of 100 μg of ADAMTS‐13 per 1 mL of 0.9% NaCl; 20 min after SAH). Neurologic performance was assessed on days 1 and 2 after SAH. Animals were killed on day 2. The amounts of subarachnoid blood, microthrombi, apoptosis and degenerative neurons were compared. The degree of neuronal inflammation and vasospasm was also compared. In five mice each (SAH and ADAMTS‐13 groups), bleeding time was assessed 2 h after SAH. Results Systemic administration of ADAMTS‐13 achieved significant amelioration of microthrombosis and improvement in neurologic performance. ADAMTS‐13 reduced the amount of apoptotic and degenerative neurons. A tendency for decreased neuronal inflammation was observed. ADAMTS‐13 did not show any significant effect on vasospasm. The degree of systemic inflammation was not changed by ADAMTS‐13 administration. ADAMTS‐13 neither increased the amount of subarachnoid blood nor prolonged the bleeding time. Conclusions ADAMTS‐13 may reduce neuronal injury after SAH by reducing microthrombosis formation and neuronal inflammation, thereby providing a new option for mitigating the severity of neuronal injury after SAH.